Intraspecific variation in mycorrhizal response is much larger than ecological literature suggests. Issue 5 (28th March 2023) - Stahlhut, Katherine N.; Conway, Megan; Mason, Chase M.; Bauer, Jonathan T.
Abstract: Mycorrhizal response is the most common metric for characterizing how much benefit a plant derives from mycorrhizal symbiosis. Traditionally, ecologists have used these metrics to generalize benefit from mycorrhizal symbiosis in plant species, ignoring the potential for plant intraspecific trait variation to alter the outcome of the mutualism. In order for mean trait values to be useful as a functional trait to describe a species, as has been attempted for mycorrhizal response traits, interspecific variation must be much larger than intraspecific variation. While the variation among species has been extensively studied with respect to mycorrhizal response traits, variation within species has rarely been examined. We conducted a systematic review and analyzed how much variation for mycorrhizal growth and nutrient response typically exists within a plant species. We assessed 28 publications that included 60 individual studies testing mycorrhizal response in at least five genotypes of a plant species, and we found that intraspecific trait variation for mycorrhizal response was generally very large and highly variable depending on study design. The difference between the highest and lowest growth response in a study ranged from 10% to 350% across studies, and 36 of the studies included species for which both positive and negative growth responses to mycorrhizae were observed across different genotypes. The intraspecific variation for mycorrhizal growth response in some of these studies was larger than the variation documented among species across the plant kingdom. Phosphorus concentration and content was measured in 17 studies and variation in phosphorus response was similar to variation in growth responses. We also found that plant genotype was just as important for predicting mycorrhizal response as the effects of fungal inoculant identity. Our analysis highlights not only the potential importance of intraspecific trait variation for mycorrhizal response, but also the lack of research that has been done on the scale of this variation in plant species. Including intraspecific variation into research on the interactions between plants and their symbionts can increase our understanding of plant coexistence and ecological stability.